Cracking the “Sugar Code”: A Snapshot of N- and O-Glycosylation Pathways and Functions in Plants Cells - Strasser, Richard; Seifert, Georg; Doblin, Monika S.; Johnson, Kim L.; Ruprecht, Colin; Pfrengle, Fabian; Bacic, Antony; Estevez, José M. (Frontiers in Plant Science, 2021)
Glycosylation is a fundamental co-translational and/or posttranslational modification process where an attachment of sugars onto either proteins or lipids can alter their biological function, subcellular location and modulate the development and physiology of an organism. Glycosylation is not a template driven process and as such produces a vastly larger array of glycan structures through combinatorial use of enzymes and of repeated common scaffolds and as a consequence it provides a huge expansion of both the proteome and lipidome. While the essential role of N- and O-glycan modifications on mammalian glycoproteins is already well documented, we are just starting to decode their biological functions in plants. Although significant advances have been made in plant glycobiology in the last decades, there are still key challenges impeding progress in the field and, as such, holistic modern high throughput approaches may help to address these conceptual gaps. In this snapshot, we present an update of the most common O- and N-glycan structures present on plant glycoproteins as well as 1) the plant glycosyltransferases (GTs) and glycosyl hydrolases (GHs) responsible for their biosynthesis; 2) a summary of microorganism-derived glycosyl hydrolases (GHs) characterized to cleave specific glycosidic linkages; 3) a summary of the available tools ranging from monoclonal antibodies, lectins to chemical probes for the detection of specific sugar moieties within these complex macromolecules; 4) selected examples of N- and O-glycoproteins as well as in their related GTs to illustrate the complexity on their mode of action in plant cell growth and stress responses processes, and finally 5) we present the carbohydrate microarray approach that could revolutionize the way in which unknown plant GTs and GHs are identified and their specificities characterized.